Peran Bank Indonesia dalam Peningkatan Kesejahteraan Umat melalui Peningkatan Value UMKM Agribisnis Perspektif Ekonomi Islam - Rosida, Ika Nazilatur; Nisak, Luluk Nur Sayidatin (Journal of Industrial and Syariah Economics, 2026)
This study aims to analyze the role of Bank Indonesia in improving community welfare by enhancing the value of agribusiness MSMEs from an Islamic economics perspective. The focus of this research is the agribusiness MSME POKTAN SUMADI in Jatiarjo Village, Prigen District, Pasuruan Regency. Agribusiness MSMEs are understood as business entities that encompass the entire chain of agricultural and plantation activities from upstream to downstream processes. The research employs a descriptive-analytical method with a correlational approach. Data collection techniques include observation, interviews, and documentation. The findings indicate that Bank Indonesia plays a strategic role and has a significant relationship in enhancing community welfare through strengthening the value of agribusiness MSMEs. This role is implemented through continuous coaching and mentoring across business processes, from production to marketing. The impact of these interventions is reflected in increased entrepreneurial independence, improved business governance, and enhanced product competitiveness. POKTAN SUMADI has obtained halal certification, developed its potential as a nature-based tourism destination, implemented systematic financial reporting, and engaged in export activities of plantation products. This study examines the role of Bank Indonesia in developing the value of agribusiness MSMEs through non-monetary empowerment programs and its integration with Islamic economic values. The implications of this study suggest that a value-based empowerment approach, encompassing independence, blessing (barakah), and halal principles, is capable of promoting sustainable community welfare.